2023
DOI: 10.1111/aos.15708
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intraretinal hyperreflective foci using multimodal imaging in eyes with age‐related macular degeneration

Abstract: PurposeThis study aimed to investigate the correspondence between intraretinal hyperreflective foci (IHRF) identified on optical coherence tomography (OCT) B‐scans with hyperpigmentation on colour fundus photography (CFP) or hyperreflectivity on infrared reflectance (IR) images in eyes with age‐related macular degeneration (AMD).MethodsFlash CFP, IR images and OCT B‐scans obtained at the same visit were evaluated. Individual IHRF identified on OCT B‐scans were assessed for the qualitative presence or absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…On eye fundus examination, they are generally detected as hyperpigmentations. Nevertheless, a recent study has demonstrated that actually only two-thirds of the intraretinal HRF present on OCT correspond to hyperpigmentations seen on the color fundus photography (CFP) [118]. HRF are widely considered displaced RPE cells, outer segment PR debris, or pigment granules [99].…”
Section: Oct Evaluation Of Drusenmentioning
confidence: 99%
“…On eye fundus examination, they are generally detected as hyperpigmentations. Nevertheless, a recent study has demonstrated that actually only two-thirds of the intraretinal HRF present on OCT correspond to hyperpigmentations seen on the color fundus photography (CFP) [118]. HRF are widely considered displaced RPE cells, outer segment PR debris, or pigment granules [99].…”
Section: Oct Evaluation Of Drusenmentioning
confidence: 99%